Extensification of Excise on Goods and Its Comparison with Other ASEAN Countries - Kasim, E S; Purwanto, T A (KnE Social Sciences, 2018)
The purpose of extending the object of goods subject to excise is to raise government revenues and regulate the circulation of goods that have negative impacts on the environment, health and society. The research method used is descriptive qualitative approach. Data obtained is the secondary data that can be used as a review and foundation by researchers to analyze the existing problems. The results of research and analysis are the basic consideration of extending the goods subject to excise through identification of feasible excise commodities and supply chain management, analysis of negative externalities and the purpose of the collection, and constraints analysis and multiplier effect. Goods subject to excise in Indonesia compared to the ASEAN countries are included in the limited form excise systems. Keywords: excise, extensification